Broadband 1H homodecoupled NMR experiments: Recent developments, methods and applications. (June 2015) - Castañar, Laura; Parella, Teodor
<x xml:space="preserve">Abstract</x> In recent years, a great interest in the development of new broadband 1H homonuclear decoupled techniques providing simplified JHH multiplet patterns has emerged again in the field of small molecule NMR. The resulting highly*‐resolved 1H NMR spectra display resonances as collapsed singlets, therefore minimizing signal overlap and expediting spectral analysis. Dr. Teodor Parella and Laura Castañar present a comprehensive compilation of the most recent advances in pure shift NMR spectroscopy, with a detailed discussion about the most relevant practical aspects in terms of pulse sequence design, selectivity, sensitivity, spectral resolution and performance. The implementation of the different reported strategies into traditional 1D and 2D NMR experiments is described and the combination with other complementary resolution‐enhanced NMR techniques opens the door of the revolutionary concept of ultra high‐resolved NMR spectroscopy. The usefulness of these novel techniques are illustrated for a number of challenging practical applications, such as the determination/ differentiation of very small chemical shift differences, analysis of highly crowded spectral regions, and the simplified and precise determination of relevant NMR parameters such as coupling constants, relaxation times or diffusion coefficients.